The composition and antimicrobial activity of leaf essential oils of selected agathosma species ( rutaceae ) - Fourie, Carla (My University, 2003)
This project was conducted to investigate properties and to record the essential oil profiles of a selection of species belonging to the genus agasthosma. Plants have been used for many years by the local South African to treat various infections and illnesses. This knowledge has largely been untapped. Buchu is one of the plant species that are used extensively by the San and Khoi people. It is remarkable that of the ca. 150 agathosma species indigenous to South Africa only two species ( Agasthosma crenulata and agathosma betulina ) have been investigated for biological activity. The genus Agasthosma is traditionally used for the following conditions ; stomach ailments, fever, coughs, cold, flu, urinary tract, and kidney infections, haematuria, prostatitis, rheumatism, gout, bruises and for antiseptic purposes.
A research report submitted to the faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine ( Pharmaceutical Affairs )
Keywords: Anti-Infective Agents; Rutaceae; Diosmin; Plant Leaves